The Effectiveness of Islamic Religious Education Subjects in the Merdeka Belajar Curriculum - Mugiyono Mugiyono; Andi Aji Saputra; M. Izharul Iman; Alif Adhi Yaksa Sudrajat; Ali Nurdin; Devita Irawati; Ravylia Puspita Samudera (UMSU, 2023)
This research is related to the lack of mutual collaboration between educators and students in the running of Islamic Education learning activities in the classroom because they have not been able to unite perceptions to achieve learning goals. Islamic Religious Education educators face challenges to implement within the framework of characteristics that include the development of soft skills and character, focus on essential materials, and flexible learning for students.Â The purpose of this research is to analyze and measure the effectiveness and strategies of Islamic Religious Education subjects in the independent curriculum.This research uses an analytical descriptive method with a qualitative approach using observation flow wrapped with interviews and questionnaire instruments totaling 20 question points containing 10 positive questions and 10 negative questions and 5 items of interview instruments to PAi subject educators at the school. This study shows positive results that there is an effect of the effectiveness of PAI subjects in the independent learning curriculum at Dharma Wanita Pare High School, seen from the results of the questionnaire instrument the majority of students answered agree and strongly agree on positive questions and vice versa for negative questions apply vice versa. Thus the alternative hypothesis (Hâ‚) is accepted or approved while the null hypothesis (HË³) is not accepted or not approved.